Policy Goals of Federalism and Decentralization in Nepal - Adhikari, Hari Prasad (NUTA Journal, 2018)
This study, descriptive and analytical in nature, aims to assess the appropriate policy goals of federalism and decentralization focusing on providing local autonomy to meet the needs of local people, improving good governance, avoiding domination of elite group and promoting inclusive democracy, reducing ethnic and cultural conflict and promoting social harmony in Nepal. The data collected through questionnaire from 350 respondents was used for analysis. Federalism seemed to be an appropriate system that deals with providing local autonomy to meet the needs of local people. The findings from this study can provide information about policy goals of local governance in Nepal. It could be helpful to provide some special guidelines to the policy makers for improving local governance. In addition appropriate policy must be adapted and sound communication/information system would be developed.